God's Servant as Potential Local Support: An Effort of Getting to Zero HIV and AIDS In East Nusa Tenggara Indonesia - Imelda F.E. Manurung (Humanistic Network for Science and Technology (HNST), 2018)
The increase in the number of HIV cases every year is the reason that HIV / VCT test is essential to prevent HIV and AIDS transmission. An HIV test is the most important entrance to prevention, care, support and treatment. East Nusa Tenggara is unique since most of its residents are very dependent on God’s servant in addition to health care. The people consider God’s servant someone who is recognized and believed to have a gift from God to cure diseases. They have potential in identifying individuals at risk of HIV and AIDS and support to take VCT. Based on this condition, this research concludes that God servant is potential local support in getting to zero HIV and AIDS. Keywords: God’s Servant, HIV and AIDS